Spinal A3 adenosine receptor activation acutely restores morphine antinociception in opioid tolerant male rats. Issue 1 (1st June 2021) - Leduc‐Pessah, Heather; Xu, Cynthia; Fan, Churmy Y.; Dalgarno, Rebecca; Kohro, Yuta; Sparanese, Sydney; Burke, Nikita N.; Jacobson, Kenneth A.; Altier, Christophe; Salvemini, Daniela; Trang, Tuan
Abstract: Opioids are potent analgesics, but their pain‐relieving effects diminish with repeated use. The reduction in analgesic potency is a hallmark of opioid analgesic tolerance, which hampers opioid pain therapy. In the central nervous system, opioid analgesia is critically modulated by adenosine, a purine nucleoside implicated in the beneficial and detrimental actions of opioid medications. Here, we focus on the A3 adenosine receptor (A3 AR) in opioid analgesic tolerance. Intrathecal administration of the A3 AR agonist MRS5698 with daily systemic morphine in male rats attenuated the reduction in morphine antinociception over 7 days. In rats with established morphine tolerance, intrathecal MRS5698 partially restored the antinociceptive effects of morphine. However, when MRS5698 was discontinued, these animals displayed a reduced antinociceptive response to morphine. Our results suggest that MRS5698 acutely and transiently potentiates morphine antinociception in tolerant rats. By contrast, in morphine‐naïve rats MRS5698 treatment did not impact thermal nociceptive threshold or affect antinociceptive response to a single injection of morphine. Furthermore, we found that morphine‐induced adenosine release in cerebrospinal fluid was blunted in tolerant animals, but total spinal A3 AR expression was not affected. Collectively, our findings indicate that spinal A3 AR activation acutely potentiates morphine antinociception in the opioid tolerant state. Abstract : Spinal A3 adenosine receptor (A3 AR) activation by MRS5698 transiently restores morphine antinociception in opioid‐tolerant rats. Intrathecal injection of MRS5698 ("on") on days 8, 9, 12, and 13 reinstates morphine antinociception. This response is blocked by A3 AR antagonist MRS1523 and absent when intrathecal vehicle ("off") is administered on days 10 and 11.